Sistem Informasi Pemeringkatan Desa PERMATA Berbasis Web Mendukung Kepesertaan BPJS Ketenagakerjaan Kudus - Dian Asriningati; Supriyono Supriyono (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The Village Care for Prosperous Workers (PERMATA) Program is a BPJS Employment program that aims to increase employment social security participation in rural areas. However, the village assessment and ranking process at the Kudus Branch of BPJS Employment is still carried out manually using spreadsheets, making data management less effective, prone to errors, and requiring a long time to prepare reports. This study aims to design a web-based PERMATA Village Ranking Information System to support a more structured and real-time village assessment process. The system was developed using the Waterfall method with the Laravel framework and MySQL database. The ranking process applies the Simple Additive Weighting (SAW) method based on predetermined assessment criteria and weights. The results of the study indicate that the system is able to simplify data management, accelerate automatic value calculations, monitor BPJS Employment membership, and produce faster, more accurate, and more transparent reports for the Kudus Branch of BPJS Employment.